PERAN GURU BIMBINGAN DAN KONSELING DALAM MENGIDENTIFIKASI PERMASALAHAN BELAJAR PESERTA DIDIK DI SMA NEGERI 1 KANDANGAN - Sri Helma Hidayati (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2017)
Research Objectives to describe the role of teacher Guidance and Counseling in identifying learning problems learners, factors causing learning problems and how to overcome learning problems faced by learners.The results showed that counseling and guidance teachers play a significant role in identifying learning problems of learners, factors causing learning problems in learners such as from within the students and from outside the students themselves. How to overcome this problem Teacher Guidance and Counseling services implement services such as classical services, information services, learning services and individual / individual counseling services.Based on the research results, the role of teacher Counseling Guidance in identifying learning problems of students in SMAN 1 Kandangan is to collect data, process data, diagnose data, perform prognosis, tretment and evaluation. Learning problems in the students such as lack of concentration, lack of understanding of subject matter, a sense of nervousness, lack of motivation, do not like subjects and from outside the learners themselves lack of facilities available in practical activities. How to overcome by providing information services, learning, individual and group. Suggestion of students should be more open and willing to consult to teachers Guidance and Counseling for learning problems they face so that can be found the solution. Teacher Guidance and Counseling should be active in providing guidance to students. The school should provide a conducive environment and complement the supporting facilities and infrastructure for the learning and teaching process.